Технологічне проєктування способів виготовлення U-подібних гвинтових поверхонь транспортних труб - Гевко, І. Б.; Рогатинський Р. М.; Комар, Р. В.; Ткаченко, І. Г.; Гупка, А. Б.; Нevko, І.; Rohatynskyi, R.; Komar, R.; Tkachenko, I.; Gypka, A. (ЦНТУ, 2025)
В роботі обґрунтовано чотири нові способи виготовлення U-подібних гвинтових поверхонь транспортних труб з використання оправ і формувальних роликів. Розроблені способи можуть реалізовуватися різними шляхами. Зокрема вминанням U-подібних рифів на готовій трубі, або одночасним навиванням та U-подібним вминанням стрічки прямокутного січення на оправу з Uподібним спіральним виступом, з подальшим скріпленням виступів навитої стрічки зварним швом. Загалом розроблені способи виготовлення U-подібних гвинтових поверхонь транспортних труб можна умовно поділити на два типи - із можливістю зміни висоти U-подібного рифу за рахунок зміни діаметр прутка пружини, та без такої можливості, в яких використовуються оправи з незмінною висотою Uподібного рифу. Також в роботі визначено і охарактеризовано конструкційні матеріалами для виготовлення гвинтових транспортних труб. У якості вихідних заготовок доцільно використовувати труби безшовні холодно- і гарачекатані, труби литі, смуговий холоднокатаний прокат. Для обох типів способів визначено і представлено раціональні конструктивно-технологічні параметри їхної реалізації. The process of technological design and manufacturing of special screw blanks is accompanied by a number of technical and production problems that require systematic analysis and comprehensive solutions. One of the main problems is the difficulty of ensuring high accuracy of the geometric parameters of screw surfaces, especially in conditions of single or small-scale production. Such surfaces have a complex spatial shape, which requires the use of specialized tools, high-precision equipment and modern control methods. Another important challenge is the choice of the optimal method of forming the workpiece depending on the material, design requirements and operating conditions. In this case, it is necessary to take into account not only technical characteristics, but also the economic feasibility of production, equipment costs, and energy intensity of the process. Another problem is achieving the required mechanical properties of the product (strength, wear resistance, fatigue endurance), which often requires the implementation of additional technological operations, in particular heat treatment or surface hardening. All these factors complicate technological planning, increase the risks of defects and increase the cost of production. Thus, the main problem is to develop rational and technically efficient technological methods that are capable of ensuring the manufacture of special screw blanks with the required characteristics at minimal production costs.
Technological Design of Methods for Manufacturing U-Shaped Helical Surfaces of Transport Pipes
Keywords: U-подібна; гвинтова поверхня; заготовка; спосіб; U-shaped; helical surface; workpiece; method